La Obligación de Información de Bienes y Derechos en el Extranjero Como Instrumento de Lucha Contra el Fraude Fiscal - García Caracuel, María (2014)
In this paper, the author analyses one of the obligations to inform recently implemented in Spain that requires from natural and legal persons to report about assets and properties abroad. Failure to comply with this requirement may make recognition of a gain over incomes and properties values not being declared. These gains will be considered income tax from last tax period.